Performance Enhancement of Solar Water Distillation Using Rectangular Aluminium Fins - Inglee P. B.; Goret V. G.; Walecha M. G.; Mahore A. W. (EPJ Web of Conferences)
This research investigates the performance enhancement of a solar water distillation system by integrating rectangular aluminium fins within a black-coated basin. The experimental setup consists of a container measuring 137.16 cm × 52 cm with a capacity of 15 litters of water, equipped with 18 aluminium fins (7 cm × 2 cm × 4 cm) inclined at 25° to the horizontal. The objective is to increase heat transfer and evaporation rates by maximizing surface area and thermal conduction. Performance comparisons were made between a finned and a non-finned system under identical solar conditions from 9:00 AM to 4:00 PM. Key parameters such as water temperature, fin temperature, solar intensity, and yield were recorded hourly. The system with fins demonstrated a significant increase in condensed water yield and thermal efficiency, achieving up to 44% efficiency and a 35–40% improvement in daily water output compared to the system without fins. These results confirm the effectiveness of fins in enhancing heat absorption and water productivity in passive solar distillation systems, making the design viable for rural and off-grid areas.